Promosi Kesehatan Diet Sehat terhadap Remaja Perempuan - Cahyaningrum, Kartika (SOCIETIES: Journal of Social Sciences and Humanities, 2025)
Abstract. Abstract Diet is a special dietary arrangement for health which is usually carried out on the instructions of a doctor or consultant with the aim of losing weight by adjusting diet and regulating the intake of certain nutrients Healthy is a condition where everything runs normally and works according to its function and as it should Diet healthy is weight loss that is done by changing behavior towards a healthier one. With these healthy diet efforts. It is hoped that the number of obese people will decrease so as to minimize the death rate due to obesity and of course someone will be more productive in carrying out their daily activities. The research method used by the researcher was an interview method by interviewing a subject who was running a healthy diet program and providing psychoeducation through posters about healthy diets. Before providing psychoeducation, the researcher first interviewed a 20-year-old student of the Faculty of Psychology, Makassar State University who had go on extreme diets. Then the researchers determined that the subjects of this study were 10 young women who went on a diet. This psychoeducation aims to provide useful information and training to change or increase the subject's understanding of a healthy diet. This psychoeducation has the benefit of providing useful knowledge and understanding to improve the subject's quality of life. The results of this study are that most of the subjects do not know what a healthy diet is and how to have a healthy diet Keywords: Healthy diet. Healthy. Psychoeducation